Squamous cell carcinoma of the thumb nail bed. - Manohar , Arumugam (Medknow Publications, 2007)
Squamous cell carcinoma arising from the nail bed is not common. This condition can be easily misdiagnosed, especially if there is preceding trauma. We present here a case of squamous cell carcinoma of the right thumb in a 70 year-old man. The distal phalanx and part of the proximal phalanx were also involved. We performed a disarticulation of the metacarpophalangeal joint of the right thumb. The wound healed well. If an early diagnosis is made, then Moh′s micrographic surgery or wide local excision with the use of a local flap could be advocated. In late stages, amputation or disarticulation is the treatment of choice.